How Obamacare Will Impact Reproductive Health - Brezina, Paul R.; Shah, Anish A.; Myers, Evan R.; Huang, Andy; DeCherney, Alan H. (Seminars in Reproductive Medicine, 2013)
For many years, health care delivery in the United States was accomplished through a complicated and evolving series of publicly and privately available insurance programs. In recent years, the increasing cost of health care as well as the relatively large number of individuals without any health care insurance coverage has prompted repeated attempts to modify or overhaul the current health care delivery paradigm. The largest legislative change to this system occurred on March 23, 2010, when President Barack Obama signed into law the Patient Protection and Affordable Care Act (PPACA).The PPACA is a multifaceted and sweeping piece of legislation. The law introduces a myriad number of changes into both public and private health insurance. Understanding the law, its implications, and how to navigate through these changes is essential to provide high-quality health care to patients. Although the law or parts of it are still at risk of being modified either through judicial or political action, it is important to recognize the current aspects of the law to understand any future modifications. Providing health care coverage in the United States is sure to be as it has always been: a constantly changing and evolving set of private and public policies that carry with them significant complexities and challenges. Health care providers must constantly strive to maximize access to and quality of medical care in whatever paradigm evolves in the future.
Keywords: patient protection and affordable care; Obamacare; health care; reproductive; infertility